Editorial (2019)
For scientific research to be considered efficient, and consequently productive, not only is it necessary to increase knowledge in academia, but also, with this, wisdom. Such wisdom must provide a fair understanding of the purposes of life, and therefore, of the proper use of science itself. Unfortunately, this is something that science cannot offer. Thus, the increase in science itself is not enough to ensure any genuine progress, even if it provides one of its ingredients.Said reasoning places, as is logical, the evaluation of science criterion outside of it. Therefore, it is appropriate to affirm that science is not isolated, but rather depends on other knowledge and human values for its fair conceptualization. For this purpose, it is important to consider that the history of science could be summarized, and in a certain way reduced, to the successive practice of replacing one explanation with another. It is in this sense that when that other explanation is available, and especially when it is considered better than the previous one, we feel a certain tranquility, harmony and intellectual satisfaction.This issue of the journal Via Inveniendi et Iudicandi offers its readers articles on the constitutional rights of minors, which we hope will be of interest to the academic community. The research context of such documents is defined by the concepts of justice, equality, peace and education.At the end, an analysis of the area of private law is included, in which the tax aspect in small businesses is analyzed.